2008
DOI: 10.3928/15428877-20080701-06
|View full text |Cite
|
Sign up to set email alerts
|

Ultrawide Angle Fluorescein Angiographic Imaging: A Comparison to Conventional Digital Acquisition Systems

Abstract: A prototype ultrawide angle imaging system displayed significantly more diabetic retinal pathology in a single image than conventional systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 8 publications
0
57
0
Order By: Relevance
“…2). Multiple studies in DR have reported that UWF FA was superior to the seven-standard fields in demonstrating angiographic abnormalities [17,29,30]. Wessel et al [30] reported that UWF FA displayed 3.9 times more nonperfusion, 1.9 times more neovascularization, and 3.8 times more panretinal photocoagulation compared with a simulated 7-field overlay.…”
Section: Clinical Applications Of Ultra-widefield Imaging Diabetic Rementioning
confidence: 99%
See 1 more Smart Citation
“…2). Multiple studies in DR have reported that UWF FA was superior to the seven-standard fields in demonstrating angiographic abnormalities [17,29,30]. Wessel et al [30] reported that UWF FA displayed 3.9 times more nonperfusion, 1.9 times more neovascularization, and 3.8 times more panretinal photocoagulation compared with a simulated 7-field overlay.…”
Section: Clinical Applications Of Ultra-widefield Imaging Diabetic Rementioning
confidence: 99%
“…Ultra-widefield FA is available in the Optos system since the P200A model provides a high-resolution wide-angle angiographic module. Single capture using a 488-nm laser with a 500-nm barrier filter enables angiographic view of peripheral vascular structure, including perfusion status, leakage, and staining, which can be missed on the seven-standard fields of the Early Treatment Diabetic Retinopathy Study [17][18][19][20]. ICGA was recently added to the multimodal capabilities of the Optos.…”
Section: Ultra-widefield Imaging Modalitiesmentioning
confidence: 99%
“…Fluorescein angiographic studies of the mid- and far-periphery of diabetic patients by Shimizu et al [13,14 ]in the 1980's demonstrated areas of peripheral retinal nonperfusion in diabetic patients. These findings have been reproduced and substantiated more recently utilizing a novel, commercially available imaging system for ultrawide-field fluorescein angiography (UWFA) that employs a scanning laser ophthalmoscope and an ellipsoidal mirror [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Second, it is among the first to utilize Optos fluorescein angiography for automated retinal imaging analysis. The medical benefit of this modality has been well documented [3] [4] [5] and its use is becoming part of standard care in many centers.…”
Section: Introductionmentioning
confidence: 99%